Born from rock: eight new species of Itauara Müller, 1888 (Trichoptera: Glossosomatidae) from southeastern Brazil, including phylogenetic and distributional comments on the genus - Alves, André Almeida; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz; Santos, Allan Paulo Moreira (European Journal of Taxonomy, 2023)
Eight new species of Itauara Müller, 1888 are described based on specimens collected in southeastern Brazil: I. bispinata sp. nov., I. caparao sp. nov., I. cipoensis sp. nov., I. cristata sp. nov., I. holzenthali sp. nov., I. mangaratiba sp. nov., I. robertsonae sp. nov., and I. rupicola sp. nov. In addition, we provided an updated distributional list of species of Itauara, with new records of I. jamesii Robertson & Holzenthal, 2011 and I. lucinda Robertson & Holzenthal, 2011 for Espírito Santo State (Brazil), I. plaumanni (Flint, 1974) for Paraná State (Brazil), and I. tusci Robertson & Holzenthal, 2011 for Minas Gerais State (Brazil). We performed an equal weighted parsimony analysis adding the new species to the dataset provided by Robertson & Holzenthal (2013), with modification of the interpretation of some morphological characters. The genus was recovered as monophyletic, but overall statistic support for clades was weak. Itauara is restricted to South America and has a disjunct distribution, with some species occurring in northern South America and others in southeastern South America. Probably, the diversification of Itauara in South America is related to the connections between the Amazon Forest and the Atlantic Forest through historical events at different times.